CEMEX : information technology, an enabler for building the future - Walker, Russell, 1972-; Feuerberg, Israel; Garcia, Lorena Sanchez; Villase?or, Santiago Trevi?o (London : Kellogg School of Management, 2017)
The case examines the role of IT in CEMEX, a giant Mexican building materials manufacturer in an industry categorized by low margins and high costs. In the early 1990s, CEMEX made significant investments in its IT systems, resulting in a data-based management operation that put it at the forefront of the industry. As the company grew through acquisitions, it integrated IT through "The CEMEX Way," a set of standardized processes, organizations, and systems implemented on a common IT platform.In 2007, when CEMEX acquired Rinker, a major Australian concrete company, aligning Rinker with CEMEX IT systems was critical to quickly streamline operations and realize efficiencies. The CIO of CEMEX had developed a new integration process called Processes & IT (P&IT) that he was considering using for the Rinker integration. However, P&IT required additional resources, including significant upfront fixed costs and investment in new personnel teams at a time when the company was already struggling with the integration of another acquisition. CEMEX could either align Rinker to The CEMEX Way or use the opportunity to invest significantly more in evolving to the new P&IT approach that focused on business process management.
Originally published in Walker, R., Feuerberg, I., Sanchez Garcia, L., & Trevi?o Villase?or, S. (2017). CEMEX: Information technology, an enabler for building the future. 5-315-502. Evanston, IL: Kellogg School of Management at Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Cemex, S.A. de C.V.; Corporations -- Technological innovations